Safety factor in the sustainable fleet management model - Rudyk Tomasz; Emilian Szczepański; Marianna Jacyna (Archives of Transport, 2019)
In the era of rapidly changing market and consumer needs, there are dynamic changes in the services offered. This also applies to the car fleet market. Currently, the approach to owning a vehicle is changing to other forms such as rental or subscription. Different types of funding are conducive to changes in the fleet management industry. More and more sophisticated services are offered for corporate clients, but also private customers. In the context of these changes, the approach to different aspects of vehicle use is also clarified, including what has been noticeable in recent years, increased interest in road safety, environmental issues and most importantly costs of use and possession of the vehicle. This puts high demands on fleet managers who sustainably need to match the structure of their fleets to the needs and capabilities of their customers while taking into account safety and ecology issues. This is a complicated task that requires decision-making assistance. This article addresses the support of the fleet manager decision, taking into account the sustainable management model. The article aimed to develop a model that takes into account the aspects of safety and ecology from the operator-financier the point of view. The result of the article is to provide a decision-making tool for the selection of vehicles and drivers, taking into account their characteristics to accomplish their tasks. The work presents the problem of fleet management, shows the characteristics of different forms of financing and the impact of market trends on the current approach to these problems. The analysis of safety aspects to the possibility of using different methods affecting its level was then presented. Another element of the article is a mathematical model of the problem of resources assignment for tasks. The developed model is universal and can be used for evaluation and optimisation. To this end, the function of the criterion has been formulated, taking into account the aspects of safety, ecology and financial aspects. It also takes into account the randomness of adverse events and the duration of the remaining appropriations in the out-of-order state. This Model can be used for the risk assessment of the driving staff. The developed model was implemented in the Flexsim environment for a computational example for a trading company. Computational experiments have indicated the correctness of the model and its high application potential, as well as further directions of model development to support complex management processes carried out by fleet managers.